2002
DOI: 10.1002/jclp.10094
|View full text |Cite
|
Sign up to set email alerts
|

The positive psychology of negative thinking

Abstract: As the positive psychology movement gains momentum, both within psychology and in the broader culture, it becomes increasingly important to ensure that the complexity of individual personality and psychological processes do not get lost in a "one-size-fits-all" approach to improving human functioning. In this article, we consider some of the ways that the costs and benefits of different kinds of optimism and pessimism may vary across different individuals, situations, and cultural contexts. We use defensive pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(189 citation statements)
references
References 28 publications
(29 reference statements)
5
172
2
3
Order By: Relevance
“…If experienced far enough in advance of a performance event, anxiety can boost effort and preparation (e.g., Norem & Chang, 2002). However, anxiety experienced immediately before or during a performance event often harms performance.…”
Section: Rituals Reduce Anxietycontrasting
confidence: 37%
“…If experienced far enough in advance of a performance event, anxiety can boost effort and preparation (e.g., Norem & Chang, 2002). However, anxiety experienced immediately before or during a performance event often harms performance.…”
Section: Rituals Reduce Anxietycontrasting
confidence: 37%
“…Norem and Chang (2002) found that a small amount of anxiety causes people to prepare more thoroughly in advance of anxiety-inducing events. In other work, Alter et al (2010) found that reappraising feelings of anxiety as excitement (i.e., reframing threats as challenges) can both improve motivation and diminish stereotype threat.…”
Section: Anxiety and Advice-taking 41mentioning
confidence: 99%
“…Optimists are more positive about what happens in their everyday lives and Peterson and Seligman's theory considers it as an attributional style that describes negative events as inconstant, external, temporary and specific (Conversano, Rotondo, Lensi, Vista, Arpone & Reda, 2010). Optimism is related to better health (mentally and physically), academic success and job performance (Hershberger, 2005) and linked to coping, satisfaction and wellbeing (Norem & Chang, 2002). Filep and Pearce (2014b) stated that optimism is possibly one of the essential values that tourists need that may even help them in dealing with unexpected events such as losing luggage.…”
Section: Introductionmentioning
confidence: 99%